TEACHING EXTENSIVE READING PROGRAM WITH CHARACTER BUILDING THEME: FROM ZERO TO HERO - Ary Setya Budhi Ningrum (Jurnal Pendidikan Karakter, 2012)
Abstract: This paper gives a try to presents the complete action plan in setting up an extensive reading course that is not only for fostering the students’ English proficiency but also for building up their character as well. This paper addresses that sets up a good theme before teaching is necessary. Henceforth, this program lies ‘from zero to hero’ as the theme. In teaching this program, a problembased approach and lexically-based language teaching are adopting and integrating as an instructional methodology. The explanation of it will be divided into two parts. First part is the review of theory underpinning the implementation of this program, and the second part is the detail of the action plan. Keywords: extensive reading, character building, problem-based approach, lexically-based language teaching PENGAJARAN PROGRAM MEMBACA EKSTENSIF DENGAN TEMA PEMBENTUKAN KARAKTER: FROM ZERO TO HERO Abstrak: Penulisan ini menyajikan rencana lengkap dalam menyelenggarakan kursus membaca ekstensif yang tidak hanya untuk mengembangkan kemampuan berbahasa Inggris para siswa tetapi juga untuk membangun karakter mereka. Makalah ini merujuk pada pentingnya menentukan tema yang baik sebelum mengajar. Untuk selanjutnya, program ini mengambil tema 'from zero to hero'. Dalam mengajar program ini, pengajaran bahasa berbasis masalah dan pengajaran bahasa berbasis leksikal diadopsi dan diintegrasikan sebagai metodologi instruksional. Penjelasan akan dibagi menjadi dua bagian. Bagian pertama adalah tinjauan teori yang mendasari pelaksanaan program ini, dan bagian kedua adalah detail dari perencanaan. Kata Kunci: membaca ekstensif, pendekatan berbasis masalah, pengajaran bahasa berbasis leksikal